Post cholecystectomy biliary gastritis and H. pylori infection - Shrestha, M.L.; Khakurel, M.; Sayami, G. (Journal of Institute of Medicine Nepal, 2007)
Background: Post cholecystectomy abdominal pain is a significant problem in a group of patients with gall stone surgery. The pathogenesis of post cholecystectomy dyspepsia is still poorly understood and yet difficult to ascertain. H. Pylori have been associated with significant number of the cases with gastritis, gastric ulcer, duodenal ulcer and other gastro -duodenal disorders. Hence, post cholecystectomy biliary gastritis associated with H. pylori infection might be a major aetiological factor. This study aims to evaluate the association of bile reflux gastritis, the presence of H. pylori and dyspeptic symptoms in post choecystectomized patients. Patients and Methods: This is a prospective non-randomized study carried out on 68 patients with post cholecystectomy dyspeptic symptoms during 2 years period through September 2002 to October 2004 in Tribhuvan University Teaching Hospital at the Department of Surgery. Results: Two hundred and thirty eight patients who were having cholelithiasis and underwent cholecystectomy were prospectively studied non-randomized way. Out of 238, 68 (28.57%) patients presented with upper abdominal pain, belching water brass with or without nausea and vomiting. So only 68 cases were included in the study. Of 68 patients, dyspeptic symptoms were more common in Bile reflux positive group (BR +)and H. pylori infection was seen in 38%(14/36) when compared with Bile Reflux negative (BR-) patients 13.75 %( 4/32), which was statistically significant. Biliary gastritis was found on 32, more over reflux esophagitis in 3 cases, duodenal ulcer in 1 case was also found on BR (-) group. H. Pylori were positive on 18 cases detected by endoscopic biopsy by giemsa stain, 14 in BR (+) and 4 in (BR-) group. Conclusion: This study suggests that excessive bile reflux may be responsible for persistence of symptoms after cholecystectomy by causing gastric mucosal damage and that biliary gastritis might be a significant problem associated with H.pylori infection in our context. Journal of Institute of Medicine Vol.27(2) 2005